1997
DOI: 10.1063/1.365357
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption of ReS2 and ReSe2 single crystals

Abstract: The optical absorption of synthetic ReS2 and ReSe2 single crystals is reported over a temperature range from 25 to 300 K. Analysis reveals that the absorption edges of ReS2 and ReSe2 are indirect allowed transitions. The indirect band gaps at various temperatures are determined and their temperature dependence is analyzed by the Varshni equation [Physica 34, 149 (1967)] and an empirical expression proposed by O’Donnel and Chen [Appl. Phys. Lett. 58, 2924 (1991)]. The parameters that describe the temperature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
36
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 19 publications
9
36
2
Order By: Relevance
“…The origin of the unpolarized spectra can be regarded as a random superposition of the E b and E ⊥ b polarization spectra. Analysis of the absorption spectra revealed that the values of energy gaps E g and E g⊥ are slightly different than the previous published works of unpolarized measurements [13,14]. The absorption anisotropy in the van der Waals planes may be a general characteristic of materials with triclinic layered structures.…”
Section: Resultscontrasting
confidence: 58%
“…The origin of the unpolarized spectra can be regarded as a random superposition of the E b and E ⊥ b polarization spectra. Analysis of the absorption spectra revealed that the values of energy gaps E g and E g⊥ are slightly different than the previous published works of unpolarized measurements [13,14]. The absorption anisotropy in the van der Waals planes may be a general characteristic of materials with triclinic layered structures.…”
Section: Resultscontrasting
confidence: 58%
“…f Ref. [24]. of the transition energy for the A 1 feature is slower than that of the A 2 transition.…”
Section: Resultsmentioning
confidence: 92%
“…This observation lends extra evidence that the A 2 feature is correlated to the band-to-band transition, but the A 1 feature is most likely related to an impurity or defect state to the conduction band. The defect or impurity center existing in the band gap of FeS 2 is temperature insensitive so that the temperature variation Table 1 Values of fitting parameters of the Varshni equation [20] and an expression proposed by O'Donnel and Chen [21] which describe the temperature dependence of the transition energies of FeS 2 The values of fitting parameters which describe the temperature dependence of indirect gaps of FeS 2 [7,16,22], and the interband transitions of other transition-metal sulfides MoS 2 [23], WS 2 [23], and ReS 2 [24] are listed for comparison. a This work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,18,19 Surprisingly, the metal-metal distances in the resulting Re 4 units are comparable to or smaller than those in bulk rhenium metal. 1 The underlying one-dimensional arrangement of rhenium in ReSe 2 leads to highly anisotropic properties in the layer plane, as revealed by studies of optical transmission and reflection normal to the layer plane [20][21][22][23][24][25] and by electron transport in bulk materials. 26 Along with this symmetry-breaking by the metal atoms, and again in contrast to MoS 2 , the chalcogen atoms are not all equally displaced above and below the Re To investigate monolayer ReSe 2 and to provide characterization tools for future work, we have recorded Raman spectra of bulk, few-layer and monolayer ReSe 2 (there are no published Raman spectra of pure ReSe 2 in any form though Raman spectra of ReS 2 have been reported 18,28 and there is one report of the Raman scattering of Mo-doped ReSe 2 29 ).…”
mentioning
confidence: 99%